New palynological and tephrostratigraphical investigations of two salt lagoons on the island of Mljet, south Dalmatia, Croatia - Jahns, Susanne; Bogaard, Christel (Vegetation History and Archaeobotany, 1998)
In the sediments of both of the investigated lakes, the tephra from the Mercato-Ottaviano eruption (Vesuvius, southern Italy) (ca. 7900 B.P.) could be identified. The palynological investigations show that from ca. 9000-7200 B.P. (8000-6000 cal B.C.) deciduous oak forests predominated, with only a few representatives of Mediterranean vegetation. At the transition to the central European Atlantic Period those forests changed to an open vegetation type, dominated byJuniperus andPhillyrea. At about 5500 B.P. (4400 cal B.C.), theJuniperus-Phillyrea vegetation was replaced byQuercus ilex woodland that still occurs on the island of Mljet today and is considered to be the natural vegetation of the Dalmatian coastland. The associated vegetation of theQ. ilex forests changed several times. At the beginning of theQ. ilex period,Juniperus values were still high, but soon they decreased andErica spread. In more recent times theQ. ilex forests were partially replaced by plantations ofPinus halcpensis. Indicators of human impact are sparse throughout the pollen record. Clear evidence for human influence exists only from ca. 3100 B.P. (1300 cal B.C.) whenJuglans andPinus halepensis were introduced to the area. Later,Olea andSecale cultivation can be suggested and further spreading ofJuniperus indicates use of the land as pasture.
Keywords: Climatic impact; human impact; Mercato-Ottaviano tephra; vegetation history; Vesuvius